(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Rickets is a metabolic bone disease that primarily affects children and is characterized by defective mineralization of the growing bone. The condition is predominantly caused by deficiencies in vitamin D, calcium, or phosphate, but may also result from genetic mutations or underlying medical conditions. This article reviews the etiology and pathogenesis of rickets in children, its clinical presentation, and current laboratory diagnostic methods. Understanding the mechanisms of rickets is crucial for early diagnosis and effective management of this preventable condition [2,4].